2014
DOI: 10.3390/bios4030204
|View full text |Cite
|
Sign up to set email alerts
|

An Inexpensive, Fast and Sensitive Quantitative Lateral Flow Magneto-Immunoassay for Total Prostate Specific Antigen

Abstract: We describe the detection characteristics of a device the Resonant Coil Magnetometer (RCM) to quantify paramagnetic particles (PMPs) in immunochromatographic (lateral flow) assays. Lateral flow assays were developed using PMPs for the measurement of total prostate specific antigen (PSA) in serum samples. A detection limit of 0.8 ng/mL was achieved for total PSA using the RCM and is at clinically significant concentrations. Comparison of data obtained in a pilot study from the analysis of serum samples with com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Wang et al (2009), Zheng et al (2012), D.B. Wang et al (2013, Shi et al (2015b), Barnett et al (2014) and Wang et al (2015) reported the use of MAR on their works, obtaining wide working ranges, high selectivity, robust assays, good sensitivity and lower limits of detection than standard AuNPs LFs. However, the intensity of the signal was related to the size of the MNPs, being the larger ones which produced higher responses being this a drawback inasmuch as it slows significantly the assay time.…”
Section: Magnetic Methodsmentioning
confidence: 99%
“…Wang et al (2009), Zheng et al (2012), D.B. Wang et al (2013, Shi et al (2015b), Barnett et al (2014) and Wang et al (2015) reported the use of MAR on their works, obtaining wide working ranges, high selectivity, robust assays, good sensitivity and lower limits of detection than standard AuNPs LFs. However, the intensity of the signal was related to the size of the MNPs, being the larger ones which produced higher responses being this a drawback inasmuch as it slows significantly the assay time.…”
Section: Magnetic Methodsmentioning
confidence: 99%
“…Biosensors based on microfabricated tin-film electrochemical sensor [31] allow detection down to a concentration of 0.12 ng mL −1 , compared with this detection method, the separable detection method using micro fluxgate assay allows samples to be conveniently and quickly changed. Due to the PSA capturing was achieved on the small glass surface; in comparison to the other biosensors [32,33] such as GMR [34] that the assay 's surface need functionalization, this assay was not contacting and immersing in chemical and bio solutions. So, the sensor can avoid being contaminated by those solutions and keep excellent stability for reuse.…”
Section: Detection Of Psa Labeled With Dynabeadsmentioning
confidence: 99%
“…Zao et al [119] improved the detection limit by two orders of magnitude for photoacoustic analysis compared to colorimetric measurements. The magnetic properties of the nanodispersed label in LFIA were recorded by Barnett et al [120], Chen et al [121], Lago-Cachon et al [122], and other authors. Several variants of LFIA with electrochemical detection are presented in the literature, the most recent of which (the work of Zhao et al [123]) is based on the use of a serial glucometer as a registrar.…”
Section: Proper Response For Lfiamentioning
confidence: 89%